La Bibbia commentata dai Padri, red. A. Di Berardino, vol I-IX, Roma 2003-2005, Città Nuova Editrice (włoska edycja amerykańskiego: Ancient Christian Commentary on Scripture vol. I-XVII, New Yersey 1998-2005, Inter Varsity Press). - Zagórski, Dariusz (Vox Patrum, 2004)
review